Contemporary management of lymph node metastases from an unknown primary to the neck: I. A review of diagnostic approaches1. Issue 1 (27th October 2011) - Strojan, Primož; Ferlito, Alfio; Medina, Jesus E.; Woolgar, Julia A.; Rinaldo, Alessandra; Robbins, K. Thomas; Fagan, Johannes J.; Mendenhall, William M.; Paleri, Vinidh; Silver, Carl E.; Olsen, Kerry D.; Corry, June; et al.
Abstract: In an era of advanced diagnostics, metastasis to cervical lymph nodes from an occult primary tumor is a rare clinical entity and accounts for approximately 3% of head and neck malignancies. Histologically, two thirds of cases are squamous cell carcinomas (SCCs), with other tissue types less common in the neck. With modern imaging and tissue examinations, a primary tumor initially undetected on physical examination is revealed in >50% of patients and the site of the index primary can be predicted with a high level of probability. In the present review, the range and limitations of diagnostic procedures are summarized and the optimal diagnostic workup is proposed. Initial preferred diagnostic procedures are a fine‐needle aspiration biopsy (FNAB) and imaging. This allows directed surgical biopsy (such as tonsillectomy), based on the preliminary findings, and prevents misinterpretation of postsurgical images. When no primary lesion is suggested after imaging and panendoscopy, and for patients without a history of smoking and alcohol abuse, molecular profiling of an FNAB sample for human papillomavirus (HPV) and/or Epstein–Barr virus (EBV) is important. Head Neck, 2013